In Julia's Kitchen : Practical and Convivial Kitchen Design Inspired by Julia Child - Heyne, Pamela; Scherer, Jim (Book collections on Project MUSE., 2017)
"An illustrated exploration of the ways in which Julia Child's kitchen design and practices influence the modern home"--